Improving the coloring of polypropylene materials for powder bed fusion by plasma surface functionalization - Gomez Bonilla, Juan Sebastian; Szymczak, Tim; Zhou, Xuemei; Schrüfer, Stefan; Dechet, Maximilian; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Additive Manufacturing, 2020)
Polypropylene (PP) powder is treated in a fluidized bed reactor with an atmospheric Ar/O2 plasma jet to investigate the influence of the plasma treatment on the coloring of the powders. The oxygen concentration in the plasma gas and duration of the treatment was varied. Contact angle and X-ray photoelectron spectroscopy measurements confirmed and quantified the formation of surface functionalities and their dependence on the process parameters. The plasma treatment contributes to a significant improvement of the dispersibility and coloring of PP. Powder bulk properties such as particle size distribution and flowability were not modified by the process. Effects of the plasma treatment on the material bulk properties are also negligible.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Color strength; Dispersibility; Plasma surface functionalization; Powder bed fusion; Powder coloring; Wettability